2009
DOI: 10.5194/hess-13-1519-2009
|View full text |Cite
|
Sign up to set email alerts
|

Observed drought and wetness trends in Europe: an update

Abstract: Abstract. Linear and nonlinear trends of drought and wetness are analysed in terms of the gridded Standardized Precipitation Index (SPI) determined from monthly precipitation in Europe (NCEP/NCAR). In characterizing the meteorological and hydrological aspects, the index is computed on a seasonal and on a bi-annual time scale. Two datasets are compared: one from 1949 to 1997 and the other one includes the update of the last decade (to February 2009). The following results are noted: (i) time series of drought a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 37 publications
(26 reference statements)
2
65
0
5
Order By: Relevance
“…Based on standardized precipitation indices (SPI), LloydHughes and Saunders (2002) found that trends in European drought over the twentieth century as a whole are generally non-significant. On the other hand, Bordi et al (2009) found a trend to increasing drought area in the latter half of the twentieth century as defined by seasonal and bi-annual SPI based on gridded re-analysis model data, although this trend is reported to have reversed more recently (21st century). Sheffield and Wood (2008b) observed non-significant changes in soil moisture droughts in Europe.…”
Section: Comparison With Trends In Climate Driversmentioning
confidence: 92%
“…Based on standardized precipitation indices (SPI), LloydHughes and Saunders (2002) found that trends in European drought over the twentieth century as a whole are generally non-significant. On the other hand, Bordi et al (2009) found a trend to increasing drought area in the latter half of the twentieth century as defined by seasonal and bi-annual SPI based on gridded re-analysis model data, although this trend is reported to have reversed more recently (21st century). Sheffield and Wood (2008b) observed non-significant changes in soil moisture droughts in Europe.…”
Section: Comparison With Trends In Climate Driversmentioning
confidence: 92%
“…However the identified signals are weak. With respect to drought analysis, Bordi et al (2009) found that strong inter-annual variability of pan-European drought indicators can render a clear identification of drought trends difficult. This is also reflected in the conclusion of a recent synthesis report on the influence of climate change on extremes, which states that there is only medium confidence of an increasing drought hazard in southern Europe (Seneviratne et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The climate change will bring even more extreme weather and climate events, including droughts in the future (IPCC 2007;van Lanen et al 2007;Bordi, Sutera 2012). Though drought impact is more evident in the low latitudes of the world (Alcamo et al 2007;UNISDR 2009) and Europe (Loyd-Hughes, Saunders 2002; Lehner et al 2005;Bordi et al 2009), but it is also an issue in the Baltic Sea region (Graham 2004;Kjellström, Ruosteenoja 2007;Barnett et al 2005;Thorsteinsson, Björnsson 2011). The awareness of drought is rising and it shows in the political agenda (IPCC 2007;UNISDR 2009;EU 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The agreement states that the Standardized Precipitation Index (SPI) should be used to characterize meteorological droughts by all National Meteorological and Hydrological Services around the world (WMO 2009). Most of the scientific investigations are concentrated on the spatial and temporal distribution of droughts (Hisdal et al 2001;Loyd-Hughes, Saunders 2002; and on the impact of droughts on hydrological cycles (Bordi et al 2009;Wilson et al 2010;Tallaksen et al 2011). Droughts are analyzed in a very wide context of scientific researches: drought impact on agro-ecosystems (Sakalauskaitė 2006;Schindler et al 2007;Kalbarczyk 2010;Rad, Zandi 2012) and on forest life (Maracchi et al 2005;Lindner et al 2007;MacKay et al 2012); interactions with water bodies (Peters et al 2006;Jakimavičius, Kovalenkovienė 2010;Hän-ninen, Vuorinen 2011) and water quality (Sakalauskiene, Ignatavicius 2003;van Vliet, Zwolsman 2008;Zielinski et al 2009).…”
Section: Introductionmentioning
confidence: 99%